2020
DOI: 10.3390/app10217839
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Prevention in Mercury-Induced Amyotrophic Lateral Sclerosis: A Case Report

Abstract: Chronic exposure to low levels of mercury is involved in the development of motor neuron diseases (MND). Genetic alterations may have a crucial role in the onset and progression. We presented a case of a TANK-binding kinase 1 (TBK1)-mutated 54-year-old male worker who developed a MND due to chronic mercury exposure at work. He was employed in a chlor-alkali plant in Central Italy. After two years of employment he had acute mercury intoxication with suggestive neurological symptoms and a high urinary level of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Forty‐two related papers [6, 7, 22–61] were summarized and it was found that 178 of 9814 patients with ALS/FTD carried TBK1 variants, including 95 patients carrying LoF variants and 83 patients carrying missense variants (Table S4). Therefore, a meta‐analysis was performed of the frequency of TBK1 variants reported in ALS/FTD patients (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐two related papers [6, 7, 22–61] were summarized and it was found that 178 of 9814 patients with ALS/FTD carried TBK1 variants, including 95 patients carrying LoF variants and 83 patients carrying missense variants (Table S4). Therefore, a meta‐analysis was performed of the frequency of TBK1 variants reported in ALS/FTD patients (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…A notable case report revealed an older man diagnosed with ALS, who had a history of chronic mercury exposure at his workplace. Further genetic testing unveiled a mutation in the TBK1 gene linked to ALS, providing a possible link between mercury exposure and neurodegenerative diseases. , Additionally, a systems biology investigation conducted on hippocampus cells exposed to methylmercury has indicated substantial alterations in proteins associated with prolonged exposure. These findings shed light on potential connections between mercury exposure and neurodegenerative conditions such as Parkinson’s disease (PD) and Alzheimer’s disease (AD) …”
Section: Mercury Toxicity On Human Health: Effects and Molecular Mech...mentioning
confidence: 99%
“…The occupational risk from metallic mercury is always combined with exposure to organic mercury present in the ecosphere, and genetic factors are critical in determining risk sensitivity or resistance. A case study is reported in which the presence of a genetic alteration in a maintenance worker from a chlor-alkali plant was associated with the recurrence of episodes of subacute mercury intoxication and finally with the appearance of amyotrophic lateral sclerosis [4].…”
Section: Knowledge On Individual Risk Factorsmentioning
confidence: 99%